Teen Dating on the Decline - Suzanna Smith (EDIS, 2012)
“Ah, the first date! This is coming up soon for some of my teenage friends. Chances are they will be excited—and nervous, too. And it’s no wonder. Child and family experts say that dating is a major change and one of the more challenging adjustments teens face.” This 2-page Family Album Radio transcript was written by Suzanna Smith and published by the UF Department of Family, Youth and Community Sciences, July 2012.